DOP11 Fibrosis and MAGNIFI-CD activity-index at MRI to predict treatment outcome in perianal fistulising Crohn's Disease patients. (27th May 2021) - Van Rijn, K; Meima-van Praag, E; Bossuyt, P; D'Haens, G; Horsthuis, K; Snijder, H; Tielbeek, J; Buskens, C; Stoker, J
Abstract: Background: The aim of this study was to evaluate degree of fibrosis and disease activity using the MAGNIFI-CD index at MRI as predictors of long-term clinical perianal fistula closure in Crohn's patients who had anti-TNF therapy and/or surgical closure. Methods: Perianal Crohn's patients who had anti-TNF and/or surgery between 2013 and 2020 with a post-treatment MRI and long-term clinical follow-up data were retrospectively included. Two radiologists scored the degree of fibrosis and items of the MAGNIFI-CD index at the post-treatment MRI. Long-term clinical closure was assessed 12 months after the post-treatment MRI and was defined as no production on palpation and/or closed external openings and absence of re-interventions. The accuracy of findings at MRI in predicting long-term clinical closure was evaluated in terms of a receiver operating characteristics (ROC) analysis. An area under the curve (AUC) with 95% confidence interval (CI) was calculated. Results: Forty-nine patients were included; 31 female, median age 33 years (IQR 26–46). Post-treatment MRI was performed at a median of 7 months (IQR 4–14) after treatment. At long-term clinical follow-up, 25 patients showed fistula closure and 24 did not. Fourteen patients showed a 100% fibrotic fistula at post-treatment MRI of which all had a closed fistula at long-term clinical follow-up (Figure 1). ROC analysis showed an AUC of 0.90 (95% CI: 0.81–0.99) for degree of fibrosis in predicting long-term clinical closure. The median MAGNIFI-CD index at post-treatment MRI was 0 (IQR 0–5) in patients with long-term clinical closure and 16 (IQR 10–20) in patients without (Figure 2). ROC analysis showed an AUC of 0.95 (95% CI: 0.89–1.00) for the MAGNIFI-CD index in predicting long-term clinical closure. Abstract DOP11 – Figure 1: Degree of fibrosis at the post-treatment MRI in relation to long-term clinical closure. Abstract DOP11 – Figure 2: MAGNIFI-CD index at the post-treatment MRI in relation to long-term clinical closure. Conclusion: Degree of fibrosis and MAGNIFI-CD index at post-treatment MRI are accurate in predicting long-term clinical closure of perianal fistulas in Crohn's patients and can be valuable parameters for radiological follow-up. A completely fibrotic tract at MRI seems a robust indicator for long-term fistula closure.